Development of case-based learning model on biochemistry online learning - Yunita Arian Sani Anwar; Mutiah Mutiah; Syarifa Wahidah Al Idrus; Eka Junaidi; Rahmawati Rahmawati (Jurnal Pijar Mipa, 2022)
The COVID-19 pandemic has changed the face-to-face learning process to online learning. It requires learning innovations that can make students more independent in exploring concepts. Case-based learning can be an alternative in the online learning process. This study aims to develop a case-based learning model in online biochemistry learning. This study uses six stages to modify the stages of development research. The results showed that the learning model developed consisted of five phases which became the syntax of the learning model developed, namely (1) Planning; (2) Orientation; (3) Organization; (4) Implementation; and (5) an evaluation developed following the results of the needs analysis. The developed syntax is described in model implementation guidelines and is equipped with learning tools. The validator's assessment shows that the model and device instructions have an index value of the expert agreement with a valid category. The test results on students showed that all the stages described in the guidelines could be implemented properly. Students gave a positive response to the implementation of case-based learning. Thus, case-based learning can be recommended for further learning.